A small amount of cyclooxygenase 2 (COX2) is constitutively expressed in platelets. (2nd January 2017) - Hu, Qianghua; Cho, Min Soon; Thiagarajan, Perumal; Aung, Fleur M.; Sood, Anil K.; Afshar-Kharghan, Vahid
Abstract: Cyclooxygenase (COX) is the rate-limiting enzyme in conversion of arachidonic acid to prostanoids, and has two isoforms, COX1 and COX2, which share 65% amino acid homology. COX1 is universally expressed in many cell types including platelets; however, expression of COX2 is known to be more limited. We examined expression of COX2 mRNA and protein in platelets and platelet-derived microparticles (MPs); using quantitative RT-PCR, immunostaining, and Western blotting. We have detected a significant amount of COX2 in platelets, both at mRNA and protein levels. We found that COX1/COX2 mRNA and protein ratios in platelets were 370:1 and 17:1, respectively. Expression level of COX2 in platelets was less than COX1, but comparable to the expression of COX2 in malignant epithelial cells. Considering the important role of COX2 in tumorigenesis and thrombosis, and the large number of circulating platelets, we propose that platelet COX2 may play an important role in physiologic and pathologic conditions.